"AGORA SOU OUTRO!”: PROPAGANDAS E EDUCAÇÃO SANITÁRIA NOS ALMANAQUES DE FARMÁCIA (1900-1945) - Lara, Caroline de (2016)
The almanacs were present among the peoples of the West to the East. Walking through the centuries, this kind of publication was diverse content, from leisurely games to moral advice, health and hygiene, being thus in a unique publication, from the fifteenth century to the present. In Brazil it was from the eighteenth century there was the spread of such material from so-called almanacs cities. In the mid-nineteenth century, the almanacs that have become the most used and consulted in the country. Through persuasion, these publications have absorbed national discussion about nationality, progress and reformulation of new Brazilian citizen, one that would safeguard the country and help you move towards a more fruitful horizon. The ideal of the Brazilian citizen was represented in advertisements of almanacs, reaching the social imaginary. Thus, such persuasive mechanisms were important tools persuasive in disseminating notions of hygiene, prevention and health education, confirming the progress of the nation project. They discussed about the diseases of the field, the city, passing by children and women. Dialogued with the speeches of rural sanitation and hygiene bodies. Thus, advertisements of almanacs were very important tools to support an ideal of upgrading the perspective of health and health education, especially during the first decades of the twentieth century.